POPULARIZATION OF JAZZ MUSIC BY JAZZMBENSENEN COMMUNITY ON THE SPOTIFY - Setiana, Rizqi Yudha; Adikara, Gilang Jiwana (Informasi, 2025)
This research aims to describe the Jazzmbensenen Community's efforts to popularize Jazz music in Yogyakarta through Spotify. Using a descriptive qualitative case study approach, the study utilizes primary data from in-depth interviews and secondary data from documentation. Data analysis involves data condensation, presentation, and conclusion drawing. The findings reveal that the Jazzmbensenen community adapts European Jazz to the local culture of Yogyakarta, incorporating local events and elements into lyrics, cover art, and album titles using a constructionist approach. This strategy eliminates the elitist stigma of Jazz, preserving its Yogyakarta roots and creating a unique, accessible character. Consequently, Jazz music becomes more approachable and enjoyable for people from all walks of life, enriched with a local flavor.   Keywords: Jazz Music, Jazzmbensenen Community, Local Culture, Popularization, Spotify.